The Protective Effect of Sweet Potato Root Tuber on Chemotherapy‐Induced Thrombocytopenia. Issue 16 (25th June 2022) - Qi, Zi‐Heng; Yan, Xiao‐Jun; Liu, Yang‐Yang; Hou, Xia; Zhao, Zhu; Zhu, Yan‐Yan; He, Ying‐Jie; Wang, Zhao‐Jie; Yang, Hong‐Jun; Na, Zhong‐Yuan; Zhao, Yun‐Li; Luo, Xiao‐Dong
Abstract : Scope: Sweet potato ( Ipomoea batatas L.) is one of the leading crops worldwide, containing high nutritional components such as fiber and polyphenols. Root tuber of Simon 1 (SIMON), a cultivar of sweet potato, is a folk food in China with a hemostasis function but lacking experimental data support. Methods and results: Now the protective effect of SIMON on chemotherapy‐induced thrombocytopenia (CIT), a serious complication of cancer treatment, is investigated for the first time by a CIT mouse model induced by intraperitoneal injection of carboplatin. As a result, SIMON raises the number of peripheral platelets, white blood cells, and bone marrow nucleated cells in CIT mice significantly. Besides, carboplatin‐induced atrophy of the thymus, spleen, and disordered metabolism of the inflammatory immune system and glycerophospholipids are also reversed by SIMON. Phytochemical analysis of SIMON indicates 16 compounds including eight phenolic derivatives, which might be associated with its anti‐CIT bioactivity. Conclusion: Sweet potato (SIMON) may be an efficient function food in the prevention of bleeding disorders. Abstract : Root tuber of sweet potato shows a protective effect on chemotherapy‐induced thrombocytopenia induced by carboplatin, supporting its traditional use to stop bleeding. The mechanism is probably involved with the restoration of metabolism of the inflammatory immune system and glycerophospholipids. And the activity of sweet potato root tuber may be due to the combined effect of the phenolic derivatives.